2023
DOI: 10.1021/acsaem.3c01020
|View full text |Cite
|
Sign up to set email alerts
|

Calcium-Decorated Polygon-Graphenes for Hydrogen Storage

Abstract: We performed first-principles calculations to investigate hydrogen (H2) storage properties of bare and calcium (Ca)-decorated polygon-graphenes, i.e., biphenylene and ψ-graphene monolayers consisting of polygons, from tetragons to octagons. In pristine forms, both biphenylene and ψ-graphene bind H2 weakly. However, upon Ca doping, biphenylene adsorbed up to five H2 molecules regardless of polygonal sites, whereas ψ-graphene anchored up to six and five H2 molecules to pentagonal and heptagonal sites, respective… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 43 publications
0
2
0
Order By: Relevance
“…Two-dimensional (2D) materials have gained attention in storage applications owing to their exceptionally unique characteristics, such as their high surface area, lightweight nature, and multiple active sites, which make them highly promising for hydrogen storage. In the pristine state, most 2D materials exhibit hydrogen binding through weak physisorption, leading to reduced capacities for hydrogen storage and restricting their functionality to low temperatures, rendering them unsuitable for practical applications. , Consequently, to enable effective storage and release under achievable storage conditions, there is a need to enhance the binding between 2D material and hydrogen, i.e., the H 2 adsorption energies onto the host material. , One approach to enhance the binding involves the functionalization of materials with metal, including alkali or alkaline metals as well as transition metals. Influenced by this notion, multiple other studies have demonstrated increased H 2 storage as a result of such modifications. For instance, Nair et al conducted experimental investigations into effective hydrogen storage using Pd-decorated g-C 3 N 4 , revealing a gravimetric density of 2.6 wt % .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Two-dimensional (2D) materials have gained attention in storage applications owing to their exceptionally unique characteristics, such as their high surface area, lightweight nature, and multiple active sites, which make them highly promising for hydrogen storage. In the pristine state, most 2D materials exhibit hydrogen binding through weak physisorption, leading to reduced capacities for hydrogen storage and restricting their functionality to low temperatures, rendering them unsuitable for practical applications. , Consequently, to enable effective storage and release under achievable storage conditions, there is a need to enhance the binding between 2D material and hydrogen, i.e., the H 2 adsorption energies onto the host material. , One approach to enhance the binding involves the functionalization of materials with metal, including alkali or alkaline metals as well as transition metals. Influenced by this notion, multiple other studies have demonstrated increased H 2 storage as a result of such modifications. For instance, Nair et al conducted experimental investigations into effective hydrogen storage using Pd-decorated g-C 3 N 4 , revealing a gravimetric density of 2.6 wt % .…”
Section: Introductionmentioning
confidence: 99%
“…These unique characteristics render it appropriate for diverse applications, such as chemical catalysis, battery application, and hydrogen storage . Earlier studies have investigated the hydrogen storage potential of alkali metals (as Li, Ca, and K) , and transition metals (as Sc, Zr, and V) , -decorated BPN. Denis et al reported the hydrogen weight percentage of Li-decorated BPN as 7.4 wt % and the average adsorption energy as 0.20 eV .…”
Section: Introductionmentioning
confidence: 99%